2011
DOI: 10.4314/wajm.v30i1.69918
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Features of Type 2 Diabetic Patients in Gaza Governorate, Gaza Strip

Abstract: Clinical and Biochemical Features of Type 2 Diabetic Patients in Gaza Governorate, Gaza Strip Aspects cliniques et biochimiques du diabète de type

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
3
13
0
2
Order By: Relevance
“…The finding that almost half of the study population had diabetes for 5 years or less does confirm the idea that type 2 diabetes has a long asymptomatic pre-clinical phase which frequently goes undetected. At the time of diagnosis, the patient could have one or more diabetes complications (Shaikh et al 2008;Yassin et al 2011). Indeed, retinopathy, CVD and neuropathy were the main diagnosed complications among our diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that almost half of the study population had diabetes for 5 years or less does confirm the idea that type 2 diabetes has a long asymptomatic pre-clinical phase which frequently goes undetected. At the time of diagnosis, the patient could have one or more diabetes complications (Shaikh et al 2008;Yassin et al 2011). Indeed, retinopathy, CVD and neuropathy were the main diagnosed complications among our diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic hyperglycemia of diabetes is associated with longterm damage, dysfunction, and failure of different organs, especially the eyes, kidneys, nerves, heart, and blood vessels. DN is one of the most severe chronic complications of diabetes and is characterized by an increased urinary albumin excretion in the absence of other renal diseases (Yassin et al 2011;Bennett and Aditya 2015). Microalbuminuria or incipient nephropathy is the earliest clinical evidence of DN (ACR of 30-300 mg/g, equivalent to timed collections of 30-300 mg/24 hours).…”
Section: Introductionmentioning
confidence: 99%
“…[29,8]. It is reported that the levels of HbA1c in the blood reflect the glucose levels to which the erythrocyte has been exposed during its lifespan [30].…”
Section: Resultsmentioning
confidence: 99%
“…These two substances along with excess triglycerides formed at the same time in liver may be discharged into blood in the form of lipoproteins [6]. In addition, disturbance in liver and kidney functions was also reported in type 2 diabetes [7][8][9]. Fat soluble vitamin-D is plays an essential role in calcium homeostasis and the maintenance of normal function in multiple tissues.…”
mentioning
confidence: 99%
“…After adjusting for age, the death rate of people with T2DM is about twice as high as their nondiabetic peers. Nearly 50-80% of all diabetics die of cardiovascular disease, stroke, or renal failure (Agewall et al, 1997 (Yassin et al, 2011). Glycated hemoglobin (HbA1c) is a routinely used marker for long-term glycemic control as an indicator for the mean blood glucose level.…”
Section: Introductionmentioning
confidence: 99%